Přestavba Brownfield - kasárna - Novák, Michal (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce řeší komplexní přestavbu stávajícího objektu kasáren, který je dlouhodobě nevyužívaný a neudržovaný – tzv. brownfield, na objekt bytového domu určeného pro cílovou skupinu obyvatel seniorského věku, kde bytové jednotky splňují stavebně technické parametry upravitelného bytu dle vyhlášky č. 398/2009 Sb., o obecných technických požadavcích zabezpečujících bezbariérové užívání staveb.

The thesis deals with a complex reconstruction of the existing building of barracks, so-called brownfield, which is not used and maintained for a long time. The reconstructed building is determined to be a residential building designated for the target population of advanced age, where the housing units meet the construction and technical parameters for an adaptable apartment according to the public notice no. 398/2009 Coll. on general technical requirements ensuring barrier-free use of buildings.
Reconstruction
Keywords: rekonstrukce; brownfield; upravitelný byt; bezbariérový; změna užívání; reconstruction; brownfield; adaptable apartment; barrier-free; change of use a building